2009
DOI: 10.1097/aln.0b013e3181bbbf9b
|View full text |Cite
|
Sign up to set email alerts
|

Aprotinin Abolishes Sevoflurane Postconditioning by Inhibiting Nitric Oxide Production and Phosphorylation of Protein Kinase C-δ and Glycogen Synthase Kinase 3β

Abstract: Aprotinin abolishes sevoflurane postconditioning, associated with inhibited phosphorylation of Akt, protein kinase C-delta, and glycogen synthase kinase 3beta and reduced nitric oxide production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…GSK3β is inactivated by phosphatidylinositol 3-kinase (PI3K)/Akt pathway and extracellular signal-regulated kinase 1/2 (Cohen and Frame, 2001). Recent studies have found that the volatile anesthetics such as isoflurane and sevoflurane induce cardioprotection by preconditioning and postconditioning (Bouwman et al, 2010;Inamura et al, 2010;Inamura et al, 2009;Kaneda et al, 2008;Okusa et al, 2009;Weber et al, 2005). Pravdic et al demonstrated that isoflurane preconditioning delays MPTP opening using the tetramethyl-rhodamine ethyl ester (TMRE) technique in rat cardiomyocytes (Pravdic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…GSK3β is inactivated by phosphatidylinositol 3-kinase (PI3K)/Akt pathway and extracellular signal-regulated kinase 1/2 (Cohen and Frame, 2001). Recent studies have found that the volatile anesthetics such as isoflurane and sevoflurane induce cardioprotection by preconditioning and postconditioning (Bouwman et al, 2010;Inamura et al, 2010;Inamura et al, 2009;Kaneda et al, 2008;Okusa et al, 2009;Weber et al, 2005). Pravdic et al demonstrated that isoflurane preconditioning delays MPTP opening using the tetramethyl-rhodamine ethyl ester (TMRE) technique in rat cardiomyocytes (Pravdic et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…After defrosting, slices were incubated at 37 °C with 1% triphenyltetrazolium chloride (Sigma Chemicals, USA) photographed, and necrotic area was determined using Adobe Photoshop ® CS (Adobe, San Jose, CA, USA) as previously described. 3 …”
Section: Determination Of Myocardial Infarct Sizementioning
confidence: 99%
“…The aorta was cannulated and hearts were perfused at 70 mmHg on a nonrecirculating isovolumic perfusion apparatus, using Krebs-Henseleit perfusate, and paced at 240 beats/min. 3 Left ventricular developed pressure (LVDP) was measured using a 2.5 French, high-fidelity micromanometer (Nihon-Kohden, Tokyo, Japan) passed into a compliant latex balloon, inserted into the left ventricle, and recorded on a PowerLab 2/20 Data Recording System (ADInstruments, Hayward, Australia). The balloon was connected to a Y-adapter with one end used to advance the micromanometer and the other to fill the left ventricular balloon with bubble-free water to an end-diastolic pressure (LVEDP) of 10 mmHg.…”
Section: Isolated Heart Perfusion and Measurement Of Functionmentioning
confidence: 99%
See 2 more Smart Citations